Advances in the Development of Non-Human Viral DNA-Vectors for Gene Delivery - Loser, P.; Huser, A.; Hillgenberg, M.; Kumin, D.; Both, G.W.; Hofimann, C. (Current Gene Therapy, 2002)
Within the last two decades, various vectors based on human viruses have been developed as gene transfer vehicles for gene therapy applications and vaccination. However, one yet unresolved problem connected to the use of viral vectors in humans is the pre-existing immunity to most of these vectors in the vast majority of the population which can result in impaired gene transfer efficiency and increased secondary toxicity. One approach to solve this problem is the development of recombinant viruses of non-human origin as vectors for gene transfer. The major rationale for using such vectors is the avoidance of vector neutralization by pre-existing antibodies directed against the virus on which the vector is based. Use of vectors based on non-human viruses may therefore allow the use of lower initial vector doses to achieve efficient gene transfer. Side-effects caused by interactions between vectors derived from human viruses with a primed immune system or with blood components could also be reduced. Furthermore, these vectors might show new cell type tropisms and could therefore infect tissues and organs that are not accessible to current viral vectors. This review outlines some of the problems inherent in the human origin of current viral vectors and describes features and progress with non-human adenovirus and baculovirus-derived vectors that may provide alternatives.
Keywords: BACULOVIRUS